Image Copyright Protection Using DigitalWatermark Based On Wavelet Transform - Sulttan, Bushra; Lafta, Muna (Iraqi Journal of Science, 2025)
Digital watermarking is a technique that can be used to embed a know piece of digital data (watermark data) within another piece of digital media (media to be protected) to act as a copyright protection and tracing for illegal copies for the digital media.In recent years, it has been recognize that embedding information in transform domain leads to more robust watermarks, so in this paper wavelet transform used as transformation domain of digital image (i.e. cover image). The main concern of the proposed watermark algorithm in this paper is to embed a watermark text in the selected color image during adaptive wavelet transformation. The embedding of the watermark text (digital 0, 1) makes by separating sequential text into different groups and hidings them in specified wavelet levels in geometric manner. The embedding and extracting techniques described in this paper, and the experimental results provided as well.